Fretful Tags Amid the Verbiage: Issues in the Representation of Modern Manuscript Material. - Neyt, Vincent (Literary & Linguistic Computing)
This article concentrates on the issue of front-end representation in an electronic genetic edition of modern manuscript material that has been transcribed using XML/TEI and, in particular, on the use to this end of XSLT within the Java XML publishing framework. The point of departure is a quote from the French genetic critic Louis Hay on genetic paper-editions in 1987: ‘It is well known that the typographic transliteration of complex manuscripts often allows only approximate solutions’ (Hay, 1987, p. 121). Can the new approach of Humanities Computing provide full solutions instead of approximate ones, or will a full solution always remain unattainable? The author argues that all the electronic editors can do is make the approximate nature of the representation explicit to users by providing more than one visualization, and by presenting users with a tool that allows them to construct their own visualization.